The seven Chinese sisters - Tucker, Kathy; Lin, Grace (Morton Grove :: Scholastic, 2003)
When a dragon snatches the youngest of seven talented Chinese sisters, the other six come to her rescue.
K
b
b
Keywords: Sisters -- Fiction; Dragons -- Fiction